Emotional Experiences of Child and Adolescent Flood Survivors in Medan Johor District, North Sumatra: A Phenomenological Study - Wardiyah Daulay; Ismail Wildansyah Siregar; Nadiyah Afrah Siregar (Talenta Publisher, 2026)
Daulay, W., Siregar, I. W., & Siregar, N. A. (2026). Emotional experiences of child and adolescent flood survivors in Medan Johor District, North Sumatra: A phenomenological study. Indonesian Journal of Medical Anthropology, 7(1), 20–25.